Reducing the blame culture through clinical audit in nuclear medicine: a mixed methods study. (January 2017) - Ross, P; Hubert, J; Wong, WL
Objectives: To identify the barriers and facilitators of doctors' engagement with clinical audit and to explore how and why these factors influenced doctors' decisions to engage with the NHS National Clinical Audit Programme. Design: A single-embedded case study. Mixed methods sequential approach with explorative pilot study and follow-up survey. Pilot study comprised 13 semi-structured interviews with purposefully selected consultant doctors over a six-month period. Interview data coded and analysed using directed thematic content analysis with themes compared against the study's propositions. Themes derived from the pilot study informed the online survey question items. Exploratory factor analysis using STATA and descriptive statistical methods applied to summarise findings. Data triangulation techniques used to corroborate and validate findings across the different methodological techniques. Setting: NHS National PET-CT Clinical Audit Programme. Participants: Doctors reporting on the Audit Programme. Main Outcome measures: Extent of engagement with clinical audit, factors that influence engagement with clinical audit. Results: Online survey: 58/59 doctors responded (98.3%). Audit was found to be initially threatening (79%); audit was reassuring (85%); audit helped validate professional competence (93%); participation in audit improved reporting skills (76%). Three key factors accounted for 97.6% of the variance in survey responses: (1) perception of audit's usefulness, (2) a common purpose, (3) a supportive blame free culture of trust. Factor 1 influenced medical engagement most. Conclusions: The study documents performance feedback as a key facilitator of medical engagement with clinical audit. It found that medical engagement with clinical audit was associated with reduced levels of professional anxiety and higher levels of perceived self-efficacy.